Higher-Order Thinking Skills in Primary School: Teachers’ Perceptions of Islamic Education - Kosasih, Aceng; Supriyadi, Tedi; Firmansyah, Mokh Iman; Rahminawati, Nan (Journal of Ethnic and Cultural Studies, 2022)
One curriculum policy in countries, including Indonesia, is to provide students with higher-order thinking skills (HOTS) to meet the challenges of the 21st century, and success in doing so is closely related to the competence of teachers in integrating HOTS in the learning process. This study investigated HOTS implementation in Islamic Education (PAI) in primary schools in Indonesia. This study employed a case study design involving 58 PAI teachers in primary schools from several West Java, Indonesia regencies. The data were collected by distributing questionnaires with short answers followed by semi-structured interviews of 10 participants. Inductive and thematic data analysis was carried out to identify, evaluate, and create themes expressed by participants with the assistance of NVivo 12. Triangulation and expert review methods were used for instrument and data validation. This study explored five findings: teacher understanding, teaching resource support, instructional strategies, and student knowledge levels. This research contributes to improving the quality of PAI learning in HOTS-oriented primary schools, and policymakers can use its findings in determining the direction of the HOTS-based PAI curriculum. Policymakers should stress the importance of increasing teacher competence in mastering the HOTS concept comprehensively in planning, implementation, and evaluation. Support from various parties in optimizing HOTS-oriented PAI learning is a necessity for teachers.